Improving outcomes in the treatment of opioid dependence (IOTOD): reflections on the impact of a medical education initiative on healthcare professionals' attitudes and clinical practice. Issue 1 (1st January 2018) - Webster, Sarah; Robinson, Sarah; Ali, Robert; Marsden, John
ABSTRACT: Since 2011, the annual improving outcomes in the treatment of opioid dependence (IOTOD) meeting has brought together a broad range of primarily European healthcare professionals as part of an ongoing effort to promote best practice for this particularly vulnerable patient population. IOTOD, a comprehensive educational initiative, includes the annual Continuing Medical Education (CME)-accredited IOTOD conference, which is dedicated to measuring practice change and outcomes resulting from attendance at its educational sessions. Following each session, delegates are asked to vote for or against incorporating specified changes into their clinical practice. These "commitments to change" have formed one measure of the effectiveness and impact of the IOTOD conference. Here, we look at why educational initiatives like the IOTOD conference are valuable, examine our methods for conducting a CME-accredited event, and highlight individualised treatment plans and delivery. We examine this approach – increasingly seen as best practice – as an example of how it may be changing attitudes and eventually affecting clinical applications in the field of opioid dependence. The measured commitments to change offer insight into HCPs' attitudes towards opioid dependence management and show that attitudes towards individualised treatment plans seem to be progressively positive, with a general consensus to incorporate psychosocial interventions.